Особливості застосування методу найменших квадратів при параметричній ідентифікації спрощеної статичної характеристики ГТД на ділянці запуску - Сіренко, Ф. Ф. (НТУ "ХПІ", 2014)
Математичне моделювання робочих процесів застосовується на етапах розробки та доведення авіаційних двигунів, зокрема при відпрацюванні програм системи автоматичного керування. В НАКУ "ХАІ" розроблено метод моделювання запуску, що базується на широкому використанні експериментальних даних та апріорних знань про об’єкт. В роботі наведено структуру моделі і алгоритм, який базується на апроксимації експериментальних даних зваженим методом найменших квадратів, що унеможливлює отримання нефізичних результатів.

Mathematical modeling of working processes is widely used during all phases of aircraft engine designing and development, particularly in developing control programs of automatic control system (ACS). Methods to model engine operation at above-idle region are well-known, but there is no common opinion about engine starting modeling. Specialists of NASU "KhAI" proposed a method to model the starting. The method is based on the intense usage of experimental data and prior knowledge about the object. The structure of the model is chosen in the way to meet best the requirements of ACS designers. Because of the structure and considerations made, the direct application of known mathematical methods is impossible, because it may lead to results that make no physical sense. The paper deals with the structure and an algorithm, which is based on approximation of experimental data by the least squares with weights. The algorithm ensures valid results.
The specificities of least square method when identifying simplified static performances of turboshaft engine at sub-idle modes
Keywords: газотурбінний двигун; стеганографія; стеганологія; стегоповідомлення; вейвлет-перетворення; mathematical model; performances of GTE; starting; algorithm; prior information